DIGITAL BRANDING UMKM MELALUI KOMUNIKASI VISUAL - Wulan Purnama Sari; Zhafirah Sholihah; Felicia Masali (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
MSME actors are often faced with a lack of understanding of the importance of branding activities, especially through social media in pandemic conditions like today. The lack of understanding of the importance of branding activities is also coupled with the lack of ability to produce good visual works for digital branding purposes. Visual works are the main key to show brand identity and also attract audiences in digital branding activities. Therefore, the team carried out PKM activities with the aim of helping MSME actors, which in this case was Bakmi Jojo, to carry out digital branding activities through visual communication works, through product photos and videos. The PKM method is carried out through training and assistance for making visual works in the form of photos and videos. The results of this visual work will be used for digital branding purposes on social media and e-commerce platforms.